Subclinical Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Relation to Office and Ambulatory Blood Pressure Measurements - Melgarejo, Jesus D.; Maestre, Gladys E.; Gutierrez, Jose; Thijs, Lutgarde; Mena, Luis J.; Gaona, Ciro; Leendertz, Reinier; Lee, Joseph H.; Chávez, Carlos A.; Calmon, Gustavo; Silva, Egle; Wei, Dongmei; et al. (Frontiers in Neurology, 2022)
BACKGROUND 24-h and nighttime blood pressure (BP) levels are stronger associated with cardiovascular risk than office or daytime BP measurements. However, it remains undocumented which of the office and ambulatory BP measurements have the strongest association and predictive information in relation to the presence of type I, or arteriolosclerosis type, cerebral small vessel diseases (CSVD). METHODS A subset of 429 participants from the Maracaibo Aging Study [aged ≥40 years (women, 73.7%; mean age, 59.3y)] underwent baseline brain magnetic resonance imaging to visualize CSVD, which included log-transformed white matter hyperintensities (log-WMH) volume and the presence (yes/no) of lacunes, cerebral microbleeds (CMB), or enlarged perivascular spaces (EPVS). Linear and logistic regression models were applied to examine the association between CSVD and each +10 mmHg increment in the office and ambulatory systolic BP measurements. Improvement in the fit of nested logistic models was assessed by the log-likelihood ratio and the generalized R2 statistic. RESULTS Office and ambulatory systolic BP measurements were related to log-WMH (β-correlation coefficients ≥0.08; P<0.001). Lacunes and CMB were only associated with ambulatory systolic BP measurements (odds ratios [OR] ranged from 1.31 [95% confidence interval, 1.10 1.55] to 1.46 [1.17-1.84], P≤0.003). Accounted for daytime systolic BP, both the 24-h (β correlation, 0.170) and nighttime (β-correlation, 0.038) systolic BP measurements remained related to log-WMH. When accounted for 24-h or daytime systolic BP levels, the nighttime systolic BP retained the significant association with lacunes (ORs, 1.05-1.06; 95% CIs, ≥1.01to≤1.13), whereas the 24-h and daytime systolic BP levels were not associated with lacunes after adjustments for nighttime systolic BP (ORs, ≤0.88; 95% CI, ≥0.77to≤1.14). On top of covariables and office systolic BP, ambulatory systolic BP measurements significantly improved model performance (1.05%≥R2≤3.82%). Compared to 24-h and daytime systolic BP, nighttime systolic BP had the strongest improvement in the model performance; for WMH (1.46% vs. 1.05%) and lacunes (3.06% vs. ≤2.05%). CONCLUSIONS 24 h and nighttime systolic BP were the more robust BP measurements associated with CSVD, but the nighttime systolic BP level had the strongest association. Controlling ambulatory BP levels might provide additional improvement in the prevention of CSVD.